Hyperferritinemia and hypoferritinemia in the context of chronic fatigue syndrome pathogenesis: a literature review and clinical implications - Kalinowska, Weronika; Kulasza, Paulina Sara; Gural, Mateusz; Jezierska, Karolina (Journal of Education, Health and Sport, 2025)
Chronic fatigue syndrome (ME/CFS) is a multifactorial, exhaustive disease entity of unclear aetiopathogenesis, the main symptom of which is prolonged, unexplained fatigue that significantly limits daily functioning. Increasing evidence suggests a link between iron metabolism, particularly ferritin levels, and the occurrence of fatigue symptoms, even in the absence of anaemia. Iron deficiency can lead to mitochondrial dysfunction, reduced energy production, cognitive decline and reduced physical performance. In patients with ME/CFS, iron supplementation, especially with ferritin ≤15 ng/ml, can result in a marked improvement in symptoms, regardless of haemoglobin levels. At the same time, studies in the post-COVID-19 syndrome patient population point to the phenomenon of hyperferritinaemia, which may be related to chronic immune system activation, endocrine disorders and increased oxidative stress. Elevated ferritin levels in this group may act not only as an inflammatory indicator, but also as an active element in the pathogenesis of chronic fatigue. A possible correlation of ferritin with increased depressive symptoms and decreased IGF-I has also been established. In light of the current data, ferritin may be an available and useful biomarker to aid in the diagnosis and differentiation of ME/CFS, both in its classic form and in the course of long COVID. However, further studies are needed to validate its diagnostic, prognostic and potentially therapeutic role.